2017
DOI: 10.11111/jkana.2017.23.4.439
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Study of e-health Literacy and Self-care Agency between Nursing Students and Non-health Department Women College Students

Abstract: Purpose:The aim of this study was to investigate e-health literacy and self-care agency of nursing students and non-health department women college students. Methods: A descriptive comparative design was used. Participants were 67 nursing students and 67 non-health department women college students between 18 and 25 years old from a university located in Seoul. Data collection was done from September 2 to October 5, 2016 using structured questionnaires. Data were analyzed using independent t-test, x 2 test, AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
5
0
2
Order By: Relevance
“…Few studies have compared eHealth usage behaviors among students studying with different majors in college. Only two studies had similar investigation in which college major was found to be a significant factor for effective eHealth usage [ 29 , 30 ]. Their findings were in line with the results of the current research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have compared eHealth usage behaviors among students studying with different majors in college. Only two studies had similar investigation in which college major was found to be a significant factor for effective eHealth usage [ 29 , 30 ]. Their findings were in line with the results of the current research.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, previous research showed that adults’ performance on using eHealth tools diversified by education and culture [ 17 ]; however, when it came to college students, few studies focused on the comparison between students from health and non-health majors. Only two articles compared the eHealth-related abilities between the health and non-health major students [ 29 , 30 ], suggesting that specialized education programs could benefit students’ eHealth-related abilities. Yet both these articles did not provide information about college students’ eHealth usage behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…e헬스 문해력 수준은 동일 도구를 사용했으나 총점 대신 평균 평점을 보고한 선행연구와 비교 시 3.78로 높았다. 즉, Park과 Kim [ 27 ]의 연구에서는 간호대생은 3.67점, 비간호대생은 3.17점으로 보고하였고, 여대생의 e헬스 문해력이 3.59점이라고 제시한 연구[ 24 ]와 의학 및 건강과학 대학생의 e헬스 문해력 수준이 24.47점이라고 보고한 연구[ 28 ]보다도 본 연구에서 높은 수준을 나타낸 바, 최근 계속해서 인터넷 활용이 증가하고 정보통신 기기가 상용화되면서 e헬스 문해력 수준이 증가하고 있는 것으로 생각된다. 한편, 본 연구의 대상자 특성에 따른 e헬스 문해력은 통계적으로 유의한 차이를 보이지 않았는데, Lee와 Nam [ 5 ]의 연구에서는 건강 관심도, 건강관리 시간에 따른 유의한 차이를 보였다.…”
Section: Discussionunclassified
“…Üstündağ (2021) tarafından ergenlere yönelik gerçekleştirilen çalışmada ise, cinsiyet açısından kız öğrencilerin esağlık okuryazarlık puanının daha yüksek olduğu saptanmıştır. Park & Kim (2017) çalışmasında, esağlık okuryazarlığı puanlarının hemşirelik bölümü öğrencileri ile sağlık bölümü dışındaki öğrenciler arasında anlamlı farklılık gösterdiği bildirilmiştir. Dashti vd.…”
Section: Tartışma Ve Sonuçunclassified